2015
DOI: 10.1111/aas.12552
|View full text |Cite
|
Sign up to set email alerts
|

Does previous chemotherapy‐induced nausea and vomiting predict postoperative nausea and vomiting?

Abstract: A history of chemotherapy-induced nausea vomiting was a strong predictor for PONV and should be investigated as an added risk factor for PONV in the preoperative period of oncology surgery in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
(32 reference statements)
0
16
1
13
Order By: Relevance
“…Our results showed that the addition of oral aprepitant to palonosetron plus dexamethasone did not reduce postoperative nausea and vomiting in female patients undergoing mastectomy and already receiving two antiemetics. However, the incidence of PONV in this study population was lower than the incidence of PONV previously reported in our institution with patients undergoing mastectomy and receiving the institutional protocol (8).…”
Section: ' Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Our results showed that the addition of oral aprepitant to palonosetron plus dexamethasone did not reduce postoperative nausea and vomiting in female patients undergoing mastectomy and already receiving two antiemetics. However, the incidence of PONV in this study population was lower than the incidence of PONV previously reported in our institution with patients undergoing mastectomy and receiving the institutional protocol (8).…”
Section: ' Discussioncontrasting
confidence: 74%
“…When it comes to breast surgery, a recent work reported 29% of nausea in the post-anesthesia care unit and 35% of post-discharge nausea and vomiting (PDNV) (7) in patients who received prophylactic antiemetic. In a previous study, the incidence of PONV in patients who underwent mastectomy was 38.1%, even with double antiemetic therapy (8). When no prophylaxis was used, the overall incidence of nausea and vomiting during the first 24 hours after surgery was reported to be 75% (9).…”
Section: ' Introductionmentioning
confidence: 95%
“…Apesar do progresso alcançado pela combinação de fármacos antieméticos considerados potentes (antagonistas serotoninérgicos e corticoesteroides), os vômitos e as náuseas incontroláveis ainda permanecem um grande desafio numa parcela desses indivíduos, mesmo em condições ideais de assistência 22 . Inclusive, nessa população, foi sugerido recentemente haver maior predisposição a NVPO 23,24 .…”
Section: Introductionunclassified
“…Portanto, em instituições que lidam com o perfil de pacientes cirúrgicos oncológicos, é razoável inferir que o manejo de NVPO permaneça como um grande desafio por se tratar de uma população constantemente submetida a cirurgias, ao uso de medicamentos quimioterápicos 23…”
Section: Introductionunclassified
See 1 more Smart Citation